MUSIC AS MORAL DRIVE TO FIND AUGUST RUSH'S PARENT IN KRISTEN SHERIDAN MOVIE AUGUST RUSH (2007): A PSYCHOANALYTIC APPROACH - Ajeng YS, Meganmextha (2011)
This study is to reveal how the moral anxiety for to find August Rush's parent of the major character, August Rush, influence his personality. The objective of the study is to analyze the movie based on the structural analysis and the psychoanalytic analysis. This study is qualitative study. The object of the study is Kristen Sheridan's August Rush. The data sources are divided into two, namely primary data source and secondary data source. In collecting in the data, the writer watches the movie and uses library research by collecting and selecting the appropriate data from many sources. The technique of the data analysis, is descriptive technique. After analyzing the movie of Kristen Sheridan's August Rush, the writer concluded that there are several aspects psychoanalytic approach of the major character. The aspect consists of id, ego, superego, an moral anxiety. The basic of August Rush to find his parent through the music, he believe the music can meet his parent because he have strong felling about his parent. The Conflict within Evan, Evan believes that their parents are waiting for him and goes to New York to find his parents. And he stays in the Wizard home. Wizard is player music on the street. The Moral anxiety in this study when Evan wants to hold a big concert in New York Philharmonic in Central Park, There is problem coming from Wizard. August knows that he will disappoint every people but the most important thing that his song will be sung in New York Philharmonic in Central Park.